Information Security as Part of the Overall Corporate Governance – It Governance - Mihaela Ungureanu (CES Working Papers, 2013)
A corporate governance system is not based solely on enforcement actions and incentives in order to obtain performance. In the context of a modern business environment, it must initiate and support research and development, contribute to social stability by harnessing human and cultural capital. Corporate governance plays a key role in improving the efficiency of the capital market through its impact on their operations and financial reporting integrity. IT governance has become a necessity due to the increased dependence, which is sometimes critical, against the company's IT resources and due to the IT risks growth and diversification that management must settle, now operating in a heavily computerized environment. The changes in the informational environment and the expansion of new information technologies in organizations determine more complex and heterogeneous IT infrastructures. An essential issue is represented by the quality and performance of the existing system within an organization.
Keywords: D82; G34; L86; 330; information security; corporate governance; IT governance Romania